Euglycemic diabetic ketoacidosis in a patient with acute stroke taking sodium glucose co-transporter 2 inhibitor. (July 2022) - Pathak, Bishnu Deep; Dhakal, Bishal; Bhattarai, Ayush Mohan; Regmi, Binit Upadhaya; Mandal, Sujit Kumar; Panta, Prashanta Raj; Khadka, Suman; Simkhada, Nabin
Abstract: Introduction: Diabetic Ketoacidosis is characterized by a triad of metabolic acidosis, hyperglycemia, and ketonemia. It is a medical emergency that needs urgent and aggressive management. In some cases, the blood glucose level may be relatively normal. Such a condition is known as Euglycemic Diabetic Ketoacidosis. Case presentation: We present a case of Euglycemic Diabetic Ketoacidosis, who was initially brought to the emergency room with the features of acute stroke. There was a diagnostic dilemma among the treating physicians due to his relatively normal blood glucose levels while he developed ketoacidosis. Discussion: Presentation of the patients includes similar to DKA such as nausea, vomiting, malaise, fatigue, and Kussmaul's respiration. The diabetic patients under sodium glucose co-transporter-2 inhibitor therapy may develop it under the setting of different precipitating factors like infection, trauma/surgery, strenuous physical exercise, fasting, alcohol intake and acute vascular events. Conclusion: Euglycemic DKA is a rare condition and its diagnosis is a challenging task. So, we should always consider it as a differential whenever any diabetic patient shows with increased anion gap metabolic acidosis with or without typical symptoms and signs. Also, we need to be aware to discontinue of SGLT-2 medication during the time of infection, surgery, severe trauma, acute illness and dehydration in the diabetic patients. Highlights: Diabetic Ketoacidosis is a medical emergency with a triad of metabolic acidosis, hyperglycemia and ketonemia. The precipitating factors includes infection, surgery, fasting, alcohol intake, acute vascular events, trauma and prolonged physical exercise. Patient presents with complaints similar to DKA such as nausea, vomiting, malaise, fatigue, and Kussmaul's respiration. Management includes fluid resuscitation, insulin infusion, dextrose and potassium supplementation.